Festivities around the world - Boix Tapia, Leonardo; CEDEC (Centro Nacional de Desarrollo Curricular en Sistemas no Propietarios) (2021)
Welcome to another fantastic and new learning adventure in which you are going to improve not only your English skills but your ICT ones too. In this project, you are going to create a practical guide to the most known festivities in the countries where English is spoken for your classmates, schoolmates and relatives. Along with this, preparing the guide you will also learn about how to express existence, obligation and prohibition in English. Try to do your best and enjoy your learning process!
DBH, 1. eta 2. mailak
Keywords: Curriculumeko baliabideak; Baliabide digitalak; Eduki digital didaktikoak; Erronketan oinarritutako ikaskuntza